Influence of flame retardant additives on the flammability behaviour of natural rubber (NR) - Ismawi Dayang Habibah Abg; Ansarifar A; Harper J F (Journal of Rubber Research, 2008)
DL
Keywords: Aluminium hydroxide; Flame retardant; LImiting oxygen index; Natural rubber; Sb2O3; Smoke density; UL-94; Zinc hydroxystannate